Zeólitas A, Y, Chabazita e seus compósitos magnéticos sintetizados a partir de cinzas volantes - Freitas, Armando Diego Lima de (2019)
Coal fly ash is found as fine particles with spherical shape as its usual shape. One of its main sources of production is the thermoelectric power plants in which, in a single unit, hundreds or even thousands of tons of this residue are generated daily. Since aluminum (Al2O3) and silicon (SiO2) oxides are the major components, these materials are potential alternative raw materials for the synthesis of zeolites, although some technical aspects need to be taken into account. This work aims the synthesis of zeolites from coal fly ash (FA) and magnetic composites generated from the incorporation of magnetic oxides, extracted from the ashes, into the zeolite structures. Thus, a prior physicochemical separation treatment of FA was required in order to remove potentially interfering materials in the synthesis of zeolites. The X-ray diffraction (XRD) analyses confirmed the formation of zeolite phases (ZA, ZY and ZC), as intended, and also confirmed the presence of these zeolite phases in the prepared composites samples. The infrared spectra indicated the presence of the interatomic bonds of the proposed materials, being possible to visualize bands belonging to each synthesized material. In the scanning electron microscopy analyses, the characteristic forms of the zeolites, cubic (ZA), hexagonal (ZC) and octahedral (ZY) were observed, as well as the spherical form of the ashes particles. The zeolites intended in this work were efficiently synthesized and preserved their crystalline properties in their respective composites with magnetic responses, conferring them potential for use in applications such as adsorption in gaseous systems and metal ions in aqueous solutions.